Diagnosis and management of neurofibromatosis type 1 in Arabian Gulf Cooperation Council Region: challenges and recommendations - Bashiri, Fahad A.; Hundallah, Khaled; Abukhaled, Musaad; Alyahya, Mossaed Mohammed; Al Futaisi, Amna; Alshowaeir, Daniah; Al Tawari, Asmaa; Abdullah, Shaker; Maaz, Ata Ur Rehman; AlShamsi, Eman Taryam; Alshuaibi, Walaa; Alotaibi, Faisal; et al. (Frontiers in Oncology, 2024)
Neurofibromatosis type 1 (NF1) is a complex multisystem genetic disorder that requires long-term, age-specific monitoring and multidisciplinary care. NF1 symptom burden can significantly affect the quality of life and impose a substantial economic burden on patients and their families. The approval and widespread availability of mitogen-activated protein kinase (MEK) inhibitors such as selumetinib for NF1-related plexiform neurofibromas have revolutionized the standard of care for patients with NF1, however their effective utilization hinges on early recognition of NF1. We present a consensus manuscript describing the challenges observed in the Arabian Gulf Cooperation Council (GCC) for diagnosing and managing NF1. Experts from the GCC also present recommendations for the early recognition and management of NF1 and its complications. A referral pathway that can play a crucial role in helping primary healthcare providers refer their patients to experts is also proposed. Increasing the availability and accessibility of genetic testing at an affordable cost and optimizing personalized NF1 care are essential for NF1 management. In addition, dDeveloping regional guidelines for NF1 management and establishing NF1 centres of excellence may facilitate better care and outcomes for patients with NF1 in the GCC region.